Ethane bridged hybrid mesoporous silsesquioxanes with sulfonic acid functionalities: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Parischa, Renu; Singh, A. P. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Periodic mesoporous organosilicas having -CH(2)-CH(2)- groups in the framewall positions and sulfonic acid groups in the pore channels were prepared using 1,2-bis(triethoxysilyl) ethane, 3-mercaptopropyltriethoxysilane and cetyltrimethylammonium surfactant, under basic conditions, by a one-pot synthesis method. XRD, N(2) sorption isotherm and TEM analysis revealed that the mesoporous structural ordering is retained after the functionalization of organic groups while solid-state NMR techniques like (13)C CP MAS NMR and (29)Si MAS NMR show the presence of sulfonic acid groups and the stability of the mesoporous framework with integrated ethane moieties as bridging groups. The hybrid material was more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts in the Claisen-Schmidt condensation of acetophenone with benzaldehyde to form chalcone.

Sulfonic acid functionalized mesoporous silicas and organosilicas: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Srilakshmi, Ch.; Parischa, Renu; Singh, A. P. (Journal of Molecular Catalysis A-Chemical, 2007)
Ethane bridged mesoporous organosilicas and MCM-41 having sulfonic acid groups in the pore channels were prepared by co-condensation method as well as grafting method, using 3-mercaptopropyltriethoxysilane (3-MPTS) as the sulfur precursor. TEM and N-2 sorption isotherm analysis revealed that the mesoporous structural ordering is retained after the functionalization and modifications of organic groups while FT-IR, Raman, XPS and solid-state C-13 CP MAS NMR shows the presence of sulfonic acid groups and the stability of the mesoporous framework. The catalytic activity of the developed materials was evaluated in the liquid phase Claisen-Schmidt condensation reaction of acetophenone with benzaldehyde, to probe the effect of mesoporous support surfaces as well as the role of preparation methods. Results showed that sulfonic acid functionalized ethane-silica samples were more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: condensation; ethane-silica; heterogeneity; sulfonic acids